The Structure-Preserving Methods for the Degasperis-Procesi Equation (Journal of Computational Mathematics, 2019)
This paper gives several structure-preserving schemes for the Degasperis-Procesi equation which has bi-Hamiltonian structures consisted of both complex and non-local Hamiltonian differential operators. For this sake, few structure-preserving schemes have beenproposed so far. In our work, based on one of the bi-Hamiltonian structures, a symplecticscheme and two new energy-preserving schemes are constructed. The symplecticity comesstraightly from the application of the implicit midpoint method on the semi-discrete system which is proved to remain Hamiltonian, while the energy conservation is derived bythe combination of the averaged vector field method of second and fourth order, respectively. Some numerical results are presented to show that the three schemes do have theadvantages in numerical stability, accuracy in long time computing and ability to preservethe invariants of the DP equation.